Probiotics: mechanism of action, health benefits and their application in food industries - Latif, Anam; Shehzad, Aamir; Niazi, Sobia; Zahid, Asna; Ashraf, Waqas; Iqbal, Muhammad Waheed; Rehman, Abdur; Riaz, Tahreem; Aadil, Rana Muhammad; Khan, Imran Mahmood; Özogul, Fatih; Rocha, João Miguel; et al. (Frontiers in microbiology, 2023)
Probiotics, like lactic acid bacteria, are non-pathogenic microbes that exert health benefits to the host when administered in adequate quantity. Currently, research is being conducted on the molecular events and applications of probiotics. The suggested mechanisms by which probiotics exert their action include; competitive exclusion of pathogens for adhesion sites, improvement of the intestinal mucosal barrier, gut immunomodulation, and neurotransmitter synthesis. This review emphasizes the recent advances in the health benefits of probiotics and the emerging applications of probiotics in the food industry. Due to their capability to modulate gut microbiota and attenuate the immune system, probiotics could be used as an adjuvant in hypertension, hypercholesterolemia, cancer, and gastrointestinal diseases. Considering the functional properties, probiotics are being used in the dairy, beverage, and baking industries. After developing the latest techniques by researchers, probiotics can now survive within harsh processing conditions and withstand GI stresses quite effectively. Thus, the potential of probiotics can efficiently be utilized on a commercial scale in food processing industries.